Second report of an official Committee appointed by the council of Ministers to enquire into relations between public corporations and the legislature, the public and the government - Council of Ministers, Federation of Nigeria (Lagos, Nigeria : Federal Government printer, 1959)
The Report was written based on the directive of the council of Ministers in May 1957, that an official committee be established to examine the statutory provisions relating to major public utility corporations and make recommendations to the council.
nmn, 26/03/19
Loans
Keywords: Federation of Nigeria; Appointments